Intercropping Forage Mulberry Benefits Nodulation and Growth of Soybeans - Xinjie Feng; Minghui Zhong; Xuexian Zhao; Xiuli Zhang; Yanbo Hu; Huihui Zhang (Agriculture)
In northern China, intercropping soybeans with forage mulberry (Morus alba L.) enhances soybean yields through the optimization of natural resource use. However, the mechanisms underlying these improvements remain largely unknown. The aim was to explore the effects of this intercropping on soybean growth and yield. We used transcriptomics, redundancy analysis, and structural equation modeling to evaluate soybean growth, yield, and nodulation; results showed that intercropping did not adversely affect plant height or stem diameter but increased chlorophyll content, photosynthetic rate, leaf area, and yield of soybean. It also increased soil available phosphorus, soil available potassium and soil water content, while reducing soil available nitrogen and the pH value. It promoted P and organic acid metabolism, transporter activity, and key-gene expression. Redundancy analysis strikingly reveals that intercropping is positively correlated with yield, gene expression and soil properties. Meanwhile, structural equation modeling analysis demonstrates that the content of available phosphorus, available potassium, and water in rhizosphere soil are positively correlated with soybean nodulation. Additionally, nodulation traits can directly enhance nitrogen metabolism, which subsequently boosts photosynthesis and ultimately exerts an indirect positive influence on soybean yield. Furthermore, intercropping soybeans with forage mulberry did not induce shade stress on the above-ground portion of soybeans but promoted its growth and nodulation.